Draft Genome Sequences of Streptococcus pneumoniae with High-Level Resistance to Respiratory Fluoroquinolones - Keness, Yoram (Genome Announc, 2016)
Streptococcus pneumoniae is the leading cause of community-acquired pneumonia. Levofloxacin is a fluoroquinolone used for treatment of severe community-acquired pneumonia. Here, we describe the draft genome sequences of S. pneumoniae with emerging resistance to levofloxacin, resulting in failure of treatment of pneumococcal pneumonia.